2018
DOI: 10.5694/mja2.12036
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin misuse‐related ambulance attendances in Victoria, 2012–2017: characteristics of patients and attendances

Abstract: Objective To compare changes in pregabalin prescribing and misuse‐related ambulance attendances; to characterise the patients attended by paramedics for pregabalin misuse‐related harms; to assess the association of pregabalin misuse with use of other sedatives and with suicidal ideation and self‐harm; to compare the characteristics of pregabalin misuse‐related harms in people who misuse pregabalin according to whether or not they also used other sedatives. Design, setting, participants Retrospective analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 19 publications
1
45
0
Order By: Relevance
“…Data are from the previously described National Ambulance Surveillance System . Briefly, electronic patient care records (ePCR), computer‐aided dispatch and other clinical details are provided to Turning Point for data cleaning, validation and coding by specialist research assistants using a systematic and validated coding method .…”
Section: Methodsmentioning
confidence: 99%
“…Data are from the previously described National Ambulance Surveillance System . Briefly, electronic patient care records (ePCR), computer‐aided dispatch and other clinical details are provided to Turning Point for data cleaning, validation and coding by specialist research assistants using a systematic and validated coding method .…”
Section: Methodsmentioning
confidence: 99%
“…Ambulance records were collected and coded as part of the Ambo Project, a collaboration between Ambulance Victoria and Turning Point (a national addiction treatment, research and education centre). The methods of this project have been described previously and are briefly outlined below.…”
Section: Methodsmentioning
confidence: 99%
“…The findings suggest that availability should be restricted by, for example, reducing pack sizes for non‐prescription paracetamol. The increasing misuse of the anticonvulsant pregabalin, widely used for treating neuropathic pain, is associated with adverse psychiatric and medical effects. In their retrospective cross‐sectional study, Crossin and her colleagues found that the rate of pregabalin‐related ambulance attendances increased tenfold in Australia between 2012 and 2017, and that the rise was correlated with the national prescription rate. Patients frequently misused pregabalin together with other sedatives, particularly benzodiazepines, and almost 40% of misuse‐related events requiring paramedic attendance were suicide attempts.…”
Section: Articles Short‐listed For the Mja Mda National Prize For Exmentioning
confidence: 99%